Growth and choice; essays in honour of U. N. Ghoshal - Ghoshal, Upendra Nath, 1886-1969; Bagchi, Amiya Kumar; Majumdar, Tapas (Oxford University Press, 1969)
Volume honoring Upendra Nath Ghosal, economist and educator.